2014
DOI: 10.3168/jds.2013-7458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking rate and calving date on dry matter intake, milk production, body weight, and body condition score in spring-calving, grass-fed dairy cows

Abstract: The primary objective of the study was to quantify the effect of stocking rate (SR) and calving date (CD) on milk production, dry matter intake (DMI), energy balance (EB), and milk production efficiency over 4 consecutive years (2009 to 2012). Two groups of Holstein-Friesian dairy cows with different mean CD were established from within the existing research herd at Moorepark (Teagasc, Ireland). Animals were assigned to either an early calving (mean CD February 14) treatment or a late calving (mean CD March 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Animal production attributes such as milk production, body condition score and body weight are negatively Figure 1 Seasonal changes in daily (mean ± s.e) CH 4 concentration from the cows in different parities correlated with the increase in stocking rate (McCarthy et al 2014). Research indicated that an increase in stocking rate results in increased grazing intensity, which will subsequently result in lower daily herbage allowance (McCarthy et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Animal production attributes such as milk production, body condition score and body weight are negatively Figure 1 Seasonal changes in daily (mean ± s.e) CH 4 concentration from the cows in different parities correlated with the increase in stocking rate (McCarthy et al 2014). Research indicated that an increase in stocking rate results in increased grazing intensity, which will subsequently result in lower daily herbage allowance (McCarthy et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The basal diet of the majority of cows was grazed grass and the data originated from a range of grazing studies (Ganche et al, 2013a,b;McCarthy et al, 2014). Individual cow DMI was periodically recorded at grass using the n-alkane technique and fecal grab samples (Dillon and Stakelum, 1989) up to 8 times across lactation.…”
Section: Datamentioning
confidence: 99%
“…), defined as the number of animals per unit area of land used during a specified period of time (Allen et al, 2011), is acknowledged as the main driver of productivity (McCarthy et al, 2014). A recent review of several SR experiments, for which there was no additional supplement fed at the highest SR, reported a 0.20 increase in milk production per ha arising from a one cow per ha increase in SR (McCarthy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SR, CD is an important determinant of feed utilization through its impact on the alignment between cow requirements and pasture supply (McCarthy et al, 2013), and altering the mean CD may have a relevant role in reducing the reliance of dairy farms on purchased feeds, particularly at high SR in early lactation (McCarthy et al, 2016). However, few studies (McCarthy et al, 2012a,b;2014) have attempted to quantify the effect of mean CD in spring on PDMI and MY or elucidate any potential interactions with SR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation